2022
DOI: 10.3389/fimmu.2022.1088725
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiling reveals different immune response patterns during general and severe Mycoplasma pneumoniae pneumonia

Abstract: Mycoplasma pneumoniae (MP) is an important human pathogen that mainly affects children causing general and severe Mycoplasma pneumoniae pneumonia (G/SMPP). In the present study, a comprehensive immune response data (33 cytokines) was obtained in school-age children (3–9 years old) during MPP, aiming to analyze the immune response patterns during MPP. At acute phase, changes of cytokines were both detected in GMPP (24/33) and SMPP (23/33) groups compared to the healthy group (p < 0.05), with 20 identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Serum concentration of IL-6 could potentially indicate the severity and outcomes of MPP [26]. Our results were similar to those of Zhang et al, with the levels of IL-2, IL-10 and IFN-γ being higher in the SMPP group than in the GMPP group (p<.05) [27]. IFN-γ is one of the major cytokines involved in the inflammatory response after M. pneumoniae infection and can increase macrophage pneumoniae infection, IL-8 was also detected.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum concentration of IL-6 could potentially indicate the severity and outcomes of MPP [26]. Our results were similar to those of Zhang et al, with the levels of IL-2, IL-10 and IFN-γ being higher in the SMPP group than in the GMPP group (p<.05) [27]. IFN-γ is one of the major cytokines involved in the inflammatory response after M. pneumoniae infection and can increase macrophage pneumoniae infection, IL-8 was also detected.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we observed the elevated serum concentrations of INF-γ, IL-2, IL-5, IL-6, IL-8, and IL-10 in patients with SMPP. ILs are a class of cytokines produced by a various of cells that play important regulatory roles in the immune system and have been implicated in the development and progression of MPP [25][26][27]. In severe pneumonia, immune cells in the lungs (e.g., macrophages and neutrophils) release interleukins, leading to an enhanced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing of neutrophils from the peripheral blood of children with MPP further confirmed the role of neutrophils, particularly neutrophil extracellular trap formation, in MPP [ 16 ]. Cytokines play critical roles in the pathogenesis of MPP, and cytokine storms are associated with MPP severity [ 31 , 32 ]. Most hub genes in the key module that expressed cytokines or chemokines and their receptors, such as IL1B, CXCL8, CCL20, CXCR2, CXCL1 , and CCRL2 , were increased in CMPP, and had a high predictive value for CMPP.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic mechanism of M. pneumoniae is complex and includes multiple aspects such as direct damage, toxin damage, and immune damage [ 22 ]. Although there are no studies showing that drug-resistant strains are directly correlated with clinical manifestation, it is shown that the rapid and massive multiplication of M. pneumoniae in the alveoli could cause direct tissue damage and blood exposure, which stimulates the body’s immune response, contributing to neutrophil and cytokine expression, which may in turn exacerbate the disease [ 23 , 24 ]. Children infected with resistant strains transferring antibiotics to tetracyclines or fluoroquinolones could significantly shorten the length of hospitalization and fever duration [ 25 , 26 ], and it is important to use glucocorticoids promptly to modulate immunity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%